Simplified mathematical modeling of hydrodynamic forces in twin-propeller ships for enhanced maneuverability during asymmetric operations - Canh, Cao Xuan; Thuy, Nguyen Thi; Anh, Nguyen Hai; Duong, Nguyen Hai (International Journal of Innovative Research and Scientific Studies, 2025)
This paper presents a novel modeling approach for representing the propulsion and steering system of twin-propeller, twin-rudder high-speed ships as an equivalent single-propeller, single-rudder system. The aim is to provide a practical method when hydrodynamic data for twin-propeller systems are limited, especially during maneuvering at high speeds. The method uses nominal size substitutions for the propellers and rudders, along with additional forces and moments, to replicate the behavior of the original system. It incorporates yaw moments derived from a measured experimental database and compares them with equivalent moments at various rudder angles to enhance the prediction of ship responses under asymmetric operations. The proposed method demonstrates good accuracy in testing the ship’s maneuvering capabilities (turning and zigzag maneuvers) compared to both real data from a high-speed warship and traditional simulation methods. The inclusion of new moment and force components derived from experimental data improved the single P&R model when applied to twin P&R ships, reducing model error by 8.4% in the case of one propeller operating at 50% capacity, and by 12.4% in the case of one propeller failure. The approach simplifies the calculation process for twin-propeller, twin-rudder systems and remains effective even with limited hydrodynamic data resulting from asymmetric operations. This method enables efficient modeling of high-speed naval ships for training simulations and supports straightforward control calculations during emergency conditions.